Error-free and error-prone lesion bypass by human DNA polymerase κ in vitro - Zhang, Yanbin (Oxford University Press, 2000)
Error-free lesion bypass and error-prone lesion bypass are important cellular responses to DNA damage during replication, both of which require a DNA polymerase (Pol). To identify lesion bypass DNA polymerases, we have purified human Polκ encoded by the DINB1 gene and examined its response to damaged DNA templates. Here, we show that human Polκ is a novel lesion bypass polymerase in vitro. Purified human Polκ efficiently bypassed a template 8-oxoguanine, incorporating mainly A and less frequently C opposite the lesion. Human Polκ most frequently incorporated A opposite a template abasic site. Efficient further extension required T as the next template base, and was mediated mainly by a one-nucleotide deletion mechanism. Human Polκ was able to bypass an acetylaminofluorene-modified G in DNA, incorporating either C or T, and less efficiently A opposite the lesion. Furthermore, human Polκ effectively bypassed a template (–)-trans-anti-benzo[a]pyrene-N(2)-dG lesion in an error-free manner by incorporating a C opposite the bulky adduct. In contrast, human Polκ was unable to bypass a template TT dimer or a TT (6-4) photoproduct, two of the major UV lesions. These results suggest that Polκ plays an important role in both error-free and error-prone lesion bypass in humans.